Working memory capacity and the retention of L2 vocabulary - Fortkamp, Mailce Borges Mota; Verçosa, Daniela Malheiros (Revista Leitura, 2019)
This sfudy examines the relationship between working memory capacity and vocabulary retention in English as a L2. The study was conducted with seventeen advanced speakers of English. Statistical analyses revealed that working memory capacity correlates significantiy with L2 vocabulary retention, This correlation was interpreted as an indication that higher spans are better able to comprehend and produce new vocabulary items in a L2 than lower spans. DOI: 10.28998/0103-6858.2007v1n39p55-74